2012
DOI: 10.1111/j.1532-5415.2012.04025.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining Prevalence and Correlates of Elder Abuse Using Promotores: Low‐Income Immigrant Latinos Report High Rates of Abuse and Neglect

Abstract: Low-income Latino immigrants are understudied in elder abuse research. Limited English proficiency, economic insecurity, neighborhood seclusion, a tradition of resolving conflicts within the family, and mistrust of authorities may impede survey research and suppress abuse reporting. To overcome these barriers, we recruited and trained promotores, local Spanish-speaking Latinos, to interview a sample of Latino adults age 66 and older residing in low-income communities. The promotores conducted door-to-door inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 23 publications
3
78
0
9
Order By: Relevance
“…Previous studies 17,18 have also confirmed this to be the most common form, while suggesting that this type of violence increases the possibility of other types of violence occurring, since it places the elderly individual in a situation of humiliation and fear, which allows the aggressor to continue or commit other types of abuse.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Previous studies 17,18 have also confirmed this to be the most common form, while suggesting that this type of violence increases the possibility of other types of violence occurring, since it places the elderly individual in a situation of humiliation and fear, which allows the aggressor to continue or commit other types of abuse.…”
Section: Discussionmentioning
confidence: 67%
“…4 However, other studies have shown that the prevalence of violence can range between 2.2% and 40.4%. 16,17 This variation in estimates could be due to the methods applied in studies and interviews, especially considering that the interview may be conducted in the presence of caregivers and/or family members. The results could also be affected by the understanding of the concept of violence of the elderly individual.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Latino health workers in Durham, North Carolina were able to overcome the multiple barriers to clinic-based HIV testing among Latino immigrants by going door-to-door to conduct rapid testing (Seña, Hammer, Wilson, Zeveloff, & Gamble, 2010). Researchers investigating elder abuse discovered that Latino seniors were more likely to disclose physical, mental, and financial abuse to promotores representing their culture and community (DeLiema, Gassoumis, Homeier, & Wilber, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Previous investigations have demonstrated that 25-33% of Latinas experience emotional abuse, which is much higher than the 4.6% reported in studies of nationally representative U.S. samples (2, 3, 4). Exposure to emotional abuse causes stress and negatively affects a woman's mental health (5, 6); nonetheless, most previous studies have only investigated emotional abuse of Latina women that is perpetrated by their husbands (7).…”
Section: Introductionmentioning
confidence: 64%